Analysis Of The Causes Of Cavitation In Centrifugal Pumps On Board KM. TLIX - Driaskoro Budi Sidharta; A Agus Tjahjono; Abid Abyan Prasetyo (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2022)
Inside the ship's engine room there is one component part, the Centrifugal Pump. At centrifugal pumps often experience a decrease in the performance of a decrease in the capacity of centrifugal pumps which results in mechanical damage to the centrifugal pump impeller and the onset of vibrations all occur due to cavitation on centrifugal pumps. Cavitation is the occurrence of vapor bubbles forming in a liquid that is flowing because the liquid pressure decreases to below the saturated vapor pressure of the liquid at the pump operating temperature. This research was conducted with the aim to find out the cause of the declining performance of centrifugal pump capacity which results in cavitation. Through this applied scientific work can find the cause of the decrease in the capacity of the ship's centrifugal pump and the results will be used as a reference or reference for fellow machinists so that the centrifugal pump on the ship can operate optimally.